2020
DOI: 10.17559/tv-20190320142210
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Accuracy and the Surface Roughness of FDM/FFF Technology and Optimisation of Process Parameters

Abstract: The work deals with the influence of process parameters on the quality and accuracy of parts produced by FDM (Fused Deposition Modelling)/FFF (Fused filament fabrication) technologies. The experiments were carried out on the 3D Ultimaker printer, PLA (Polylactid Acid) thermoplastics were used as the test materials. The practical part is divided into 3 experiments. First, the optimum temperature was set. In the next part, the parameters of retraction rate, retraction length and crossing speed were determined. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In general, the experimental studies confirm that layer height is critical for surface roughness (Pérez et al , 2018), but the effect of other printing parameters on surface roughness is not well known yet. For instance, Mendricky and Fris (2020) identified the influence of printing speed on surface roughness, whereas Yang et al (2020) found that this factor did not influence this output. Consequently, there is still a research gap that requires more testing to validate published findings.…”
Section: Related Workmentioning
confidence: 99%
“…In general, the experimental studies confirm that layer height is critical for surface roughness (Pérez et al , 2018), but the effect of other printing parameters on surface roughness is not well known yet. For instance, Mendricky and Fris (2020) identified the influence of printing speed on surface roughness, whereas Yang et al (2020) found that this factor did not influence this output. Consequently, there is still a research gap that requires more testing to validate published findings.…”
Section: Related Workmentioning
confidence: 99%
“…It plays an important role as higher retraction speeds can result in stringing issues, whereas lower speeds can lead to the generation of blobs within the print. 65 A retraction speed of 25 mm/s has been adopted for this work. Lastly, Printing speed depicts the motion of the axes motors as well as the extruder motors.…”
Section: D Printing Of Specimensmentioning
confidence: 99%
“…Galietto et al [ 5 ] and Mendicky et al [ 6 ] considered processing parameters such as deposition speed, layer height and infill density. Surface roughness was significantly influenced by these factors, according to the external geometry of the parts.…”
Section: Introductionmentioning
confidence: 99%